G65(P) Risk of invasive pneumococcal disease in children with sickle cell disease in the era of pneumococcal conjugate vaccines: a systematic review of the literature. (12th March 2018) - Oligbu, G; Pay, L; Fallaha, M; Oligbu, O; Nwaomu, U
Abstract : Introduction: Invasive pneumococcal disease (IPD) is the leading cause of morbidity and mortality in children with sickle cell disease (SCD). 7-valent pneumococcal conjugate vaccine (PCV7) was first introduced in 2000 in US and at various times in other countries. It was replaced by 13-valent pneumococcal conjugate vaccines (PCV13) in 2010. This PCV are highly effective in preventing IPD in children with SCD. The risk of IPD has not been systematically assessed in children with SCD since the introduction of PCV. Methods: We undertook a systematic review of the English literature published from 2000 to October 2017 to evaluate the risk factors, serotype distribution, clinical presentation and outcomes of IPD in children with sickle cell disease. Data sources included MEDLINE, EMBASE Cochrane library, and references within identified articles. Results: We identified 475 potential studies, of which 66 were duplicates. A further 299 were excluded on the basis of title and abstracts and another 94 studies did not meet eligibility criteria on full-text screening. We included 16 publications involving 11 383 children less than 21 years-olds with SCD. A total of 161 (1.4%) IPD was identified: 147 homozygote for haemoglobin S (HbSS), 10 double heterozygote for haemoglobin S and C (HbSC) and 4 others. Among the nine studies reporting clinical presentation, septicaemia was the commonest (n=69/108; 63.8%) followed by pneumonia (n=20/108; 18.5%). The serotypes associated with IPD in SCD were mainly non-PCV13 (n=117/133; 88%), of which more than a quarter was due to serogroup 15A/B/C (n=34/117; 29%, ). Serotype 23 F (n=6/16, 37.5%) and 7 F (n=4/16; 25%) were the main vaccine serotypes. Majority were sensitive to penicillin and ceftriaxone. The crude case fatality rate was 11.2% (n=18/161). Conclusions and clinical implications: This report demonstrates the effectiveness of conjugate vaccines to reduce the rate of IPD in children with SCD. However, these children remain at increased risk and are also more likely to die of their infection compared to their peers without SCD. Most IPD cases are now due to serotypes not covered by PCV13. Therefore better prevention strategies are needed to reduce the overall burden IPD in children with SCD.